Developing Foreign Language Communicative Competence for English Business Meetings Using Business Meeting Simulations - Mateja Dostal (Scripta Manent)
This article reports on the analysis of business meeting simulation data investigating the use of Business English (BE) in business meeting simulations at the Faculty of Economics, University of Ljubljana, Slovenia. The research explores the use of business meeting simulations in a higher education setting in order to bring into focus how patterns of linguistic interactions among BE students are structured, with and without a BE teacher’s corrective feedback. The findings provide possible solutions for the effective integration of business meeting simulations into BE programmes to improve students’ performance in international business meetings in which English is the lingua franca by using business meeting simulations as a BE teaching tool. Corpus analysis and qualitative analysis of linguistic, sociolinguistic and pragmatic elements of foreign language communicative competence (FLCC) were used to explore the development of FLCC elements of BE students in the spoken corpus of English business meeting simulations. The main finding of the study is that whilst repeated business meeting simulation practice may provide BE students with a certain concrete experience of this communicative context even without a teacher’s corrective feedback, practice without corrective feedback does not facilitate the correct and comprehensive development of FLCC.